A rapid and selective synthesis of α, α-fluorohalo esters via fluorohalogenative or difluorinative hydration of ynol ethers. Issue 93 (1st October 2015) - Hu, Liang; Che, Chao; Tan, Ze; Zhu, Gangguo
Abstract : A Selectfluor-mediated fluorohalogenative or difluorinative hydration of ynol ethers is described, giving various α, α-fluorohalo esters including α, α-bromofluoro, α, α-chlorofluoro, α, α-fluoroiodo, and α, α-difluoro esters in a highly selective manner under mild reaction conditions. Abstract : A Selectfluor-mediated fluorohalogenative or difluorinative hydration of ynol ethers is described, giving various α, α-fluorohalo esters including α, α-bromofluoro, α, α-chlorofluoro, α, α-fluoroiodo, and α, α-difluoro derivatives in a highly selective manner under very mild reaction conditions. The resultant products can be applied to the facile synthesis of α-monofluoro-α-amino acids. This reaction represents a new advance in the trifunctionalization of alkynes.